Analisis Ekonomi Pencegahan Pressure Injury (Oral Nutrition, Repositioning, Skin Protection): Literature Review - Tarigan, Sumiati; Yusuf, Saldy; Syam, Yuliana (Jurnal Keperawatan Muhammadiyah, 2019)
Introduction: Pressure injury is a major problem in patients with long bed rest. At least the pressure injury has an impact on patients, families and health workers, which is one of the causes of morbidity in patients both physically and mentally, resulting in high health expenses, and an increase in nurses' workload. So it is necessary to take precautionary measures that include oral nutrition, repositioning and skin protection that are fairly expensive. This literature review wants to describe the amount of costs needed to prevent pressure injury.Method: Data is collected since 2017, using 3 databases (Pubmed, science direct, goggle schollar) where the literature used is published internationally, additional references are taken from the bibliography of all relevant articles. Inclusion criteria refer to the modality of prevention of injury injury and the costs required.Result: The average cost required for oral nutrition is AU $ 33,687 compared to standard care, namely AU $ 425 in 1 year, the total cost incurred due to pressure injury was $ 96,552 for 10 months, with an average of $ 9655 / month, and use of skin protection assessed most cost effective. Conclusion: Although it is considered relatively expensive, prevention of pressure injury provides an economic benefit of 87% compared to treatment